2015
DOI: 10.3184/174751915x14246963094093
|View full text |Cite
|
Sign up to set email alerts
|

The aromatisation of terpenes and steroids by dehydrogenation

Abstract: The formation of aromatic compounds by the dehydrogenation of terpenes and steroids and some of the current uses of the products are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Previous studies on the vulcanization of limonene show compelling evidence for the formation of volatile by-products especially at high temperatures >140 °C, 15,45 namely cyclic monosulfides (Fig. 3, (4)–(7)) and hydrocarbons ( e.g.…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies on the vulcanization of limonene show compelling evidence for the formation of volatile by-products especially at high temperatures >140 °C, 15,45 namely cyclic monosulfides (Fig. 3, (4)–(7)) and hydrocarbons ( e.g.…”
Section: Resultsmentioning
confidence: 87%
“…The formation of perylene is usually associated with the transformation of terrigenous and/or marine OM during microbial processes in reducing environments, or the release of water fungi products during the destruction of wood [105][106][107]. Previous studies have shown that phenanthrene structures may be associated with diterpene transformation [108] or may form by the dehydrogenation of sterols [109]. The ratio of diterpenoid diagenetic products, methylphenanthrenes (MPI1; Table 2; [110]), is based on different thermodynamic stability and bioavailability of the main four isomers (3MP, 2MP, 9/4MP, 1MP).…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…As shown in Figure 1, pimaranes are slightly different in basic structure and stereochemistry if compared to abietanes and most importantly, lacking of conjugated C=C bonds, they do not contribute significantly to oxidation reactions. Conversely, degradation of colophony and Venice turpentine is predominantly the result of the oxidation and dehydrogenation of conjugated dienes of the abietane moiety [31]. Highly oxidized DABA compounds resulting from dehydrogenation of ABA were found in old painting varnishes [32][33] [34] and Stradivari's instruments [4].…”
Section: Colophonymentioning
confidence: 99%